Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.2139/ssrn.1407162
|View full text |Cite
|
Sign up to set email alerts
|

Government Information Transparency

Abstract: This paper studies a model of announcements by a privately informed government about the future state of economic activity in an economy subject to recurrent shocks and with distortions due to income taxation chosen by majority voting. Although transparent communication would ex-ante be desirable, we find that even a benevolent government may decide to be non-informative in an attempt to countervail the tax distortion in a second-best type of policy. In a politico-economic (Nash) equilibrium, transparency crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 62 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…For example, an elected government might be influenced by lobbying activity or by a demand for redistribution. In Albornoz, Esteban, and Vanin (), we have explored the latter possibility and have shown that inequality reduces transparency because it generates higher taxes. This finding modifies the results obtained in Section , where we have shown how the effects of inequality on transparency depend on labor supply elasticity.…”
Section: Concluding Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For example, an elected government might be influenced by lobbying activity or by a demand for redistribution. In Albornoz, Esteban, and Vanin (), we have explored the latter possibility and have shown that inequality reduces transparency because it generates higher taxes. This finding modifies the results obtained in Section , where we have shown how the effects of inequality on transparency depend on labor supply elasticity.…”
Section: Concluding Discussionmentioning
confidence: 99%
“…This can be seen most clearly in Albornoz, Esteban, and Vanin (), where mixed strategies allow for a semiseparating equilibrium.…”
mentioning
confidence: 88%
See 1 more Smart Citation